Hospitality and Travel Marketing - Morrison, Alastair M. (Australia Delmar, Thomson Learning, 2002)
For those who are seeking a career in hospitality, travel, tourism, this [book] expresses the relationship between marketing and the tourism industry, and emphasizes a broader marketing perspective through collaborative efforts between hotels, airlines, restaurants, and travel agencies. Written to engage readers in understanding all aspects of marketing, some of the topics covered include: research and analysis; plans and strategies; marketing segmentation and trends; product development; partnership; people and service; packaging; the distribution mix and the travel trade; communications; advertising; sales promotion and merchandising; sales management; personal selling; public relations; and pricing and evaluation. The book is organized around the Hospitality and Travel Marketing System model which serves as a guide to understanding marketing functions and related techniques.-Back cover.
Include Index, Appendix and Glossary and Illustration
Keywords: Tourism--Marketing -- Hospitality industry--Marketing -- Motels--Marketing